Genetic algorithm optimization applied to electromagnetics: a review - Weile, D.S.; Michielssen, E. (IEEE transactions on antennas and propagation, 1997)
Genetic algorithms are on the rise in electromagnetics as design tools and problem solvers because of their versatility and ability to optimize in complex multimodal search spaces. This paper describes the basic genetic algorithm and recounts its history in the electromagnetics literature. Also, the application of advanced genetic operators to the field of electromagnetics is described, and design results are presented for a number of different applications.